2016
DOI: 10.1016/j.ijcard.2016.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Provoking conditions, management and outcomes of type 2 myocardial infarction and myocardial necrosis

Abstract: Background Type 2 myocardial infarction (MI) is defined as myocardial necrosis (myonecrosis) due to an imbalance in supply and demand with clinical evidence of ischemia. Some clinical scenarios of supply-demand mismatch predispose to myonecrosis but limit the identification of symptoms and ECG changes referable to ischemia; therefore, the MI definition may not be met. Factors that predispose to type 2 MI and myonecrosis without definite MI, approaches to treatment, and outcomes remain poorly characterized. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 28 publications
3
48
1
2
Order By: Relevance
“…Categorization of MI by type has increased over time, but the International Classification of Diseases (ICD) coding system lacks distinct categories for T2MI 32 likely limiting capture in clinical settings. However, non-specific ICD-9 411.89 and ICD-10 I24.8 codes “other acute and subacute forms of ischemic heart disease” have been used for this purpose 33 . Lack of data on MI type has been attributed to the relatively recent introduction of the Universal Definition of MI, presumed under-reporting of T2MI, and lack of consistency in T2MI criteria 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Categorization of MI by type has increased over time, but the International Classification of Diseases (ICD) coding system lacks distinct categories for T2MI 32 likely limiting capture in clinical settings. However, non-specific ICD-9 411.89 and ICD-10 I24.8 codes “other acute and subacute forms of ischemic heart disease” have been used for this purpose 33 . Lack of data on MI type has been attributed to the relatively recent introduction of the Universal Definition of MI, presumed under-reporting of T2MI, and lack of consistency in T2MI criteria 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common presumed T2MI causes in the Danish study were anemia, arrhythmias, and respiratory failure 22 . A New York study found surgery, anemia, and sepsis were common 33 . Arrhythmias were also a common presumed T2MI cause in several general population studies 21,28,35 .…”
Section: Discussionmentioning
confidence: 99%
“…We used ICD‐9 codes to define NSTEMI patients, regardless of whether they underwent angiography, and thus were able to evaluate the effect of type 2 MI on hospital‐level MI metrics. Smilowitz et al attempted to distinguish type 2 MI using the Third Universal Definition; however, their study was limited to a comparison between type 2 MI and myocardial injury . In a recently published study, Neumann et al enrolled 1548 patients (188 with type 1 MI and 99 with type 2 MI) who presented with suspected MI and used the Third Universal Definition to distinguish type 1 from type 2 MI .…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 MI is common and has been associated with worse prognosis. [3][4][5][6] Although there has been widespread acceptance of the concept of type 2 MI, the current International Classification of Diseases (ICD) coding system does not recognize type 2 MI as a separate entity; therefore, its impact on hospital-level MI outcomes has not been studied because these patients continue to be categorized under the general umbrella of non-ST-segment-elevation myocardial infarction (NSTEMI). Compounding this is the fact that guidelines-based post-ACS treatment is expected to be followed in all patients with a diagnosis of MI.…”
mentioning
confidence: 99%
“…10,29 Rates of obstructive CAD in T2MI patients undergoing coronary angiography range from 28% to 78%. 3,8,9,27 Despite a high prevalence of CAD in these patients, significant disparities exist in medical management of even those with CAD in T2MI or myocardial injury, when compared with those with T1MI 1,3,4,[8][9][10][11][12]14,15,[19][20][21][22][23][24][25][26][27] (Table 2).…”
Section: Introductionmentioning
confidence: 99%